EFFECT OF REWARD AND JOB COMFORT ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE (CASE STUDY: PT. MERAKI DIGITAL INDONESIA) - Adam Hasbi Nugroho; Muhammad Havidz Aima (Dinasti International Journal of Education Management And Social Science, 2022)
This study aims to identify and explain the effect of reward and job comfort against employee performance with job satisfaction as a mediating variable (Case Study: PT. Meraki Digital Indonesia). This research is a quantitative research with 420 employees of PT. Meraki Digital Indonesia as a population. The sampling technique is non-probability sampling with 150 permanent employees as a sample. Data sources from primary and secondary data. The data analysis method uses SEM-PLS with SmartPLS software 3.2.9 version. The results showed that: (1) Reward and job comfort both partially and simultaneously has a positive and significant effect on job satisfaction; (2) Reward, job comfort, and job satisfaction both partially and simultaneously has a positive and significant effect on employee performance; and (3) Job satisfaction has a positive and significant effect in mediating reward and job comfort on employee performance.